Production and characterization of activated carbon based on coffee husk residue for phosphate removal in aqueous solutions - Cruz J.F. (2019)
ZnCl2-activated carbon was prepared using coffee husk for phosphate adsorption in aqueous solutions. Textural, morphological and structural analyses were carried out to characterize the produced materials. XRD detected the presence of ZnO in the activated carbon structure, and the measured nitrogen isotherm showed a micro-macroporous structure with 989 m2/g of specific surface area for this material. Phosphate equilibrium and kinetic experiments were conducted. Equilibrium data fit best to the Dubinin-Radushkevich model (r2≥0.96), with maximum adsorption capacities of 59.38 – 63.87 mg P/g in the pH range between 5 and 9. Intraparticle diffusion was the rate-limiting mechanism of the adsorption.